2004
DOI: 10.21273/hortsci.39.3.595
|View full text |Cite
|
Sign up to set email alerts
|

Phytotoxicity of Several Iron Fertilizers and Their Effects on Fe, Mn, Zn, Cu, and P content of African Marigolds and Zonal Geraniums

Abstract: Zonal geraniums (Pelargonium ×hortorum) from seed and african marigolds (Tagetes erecta), which are known to be highly susceptible to Fe toxicity problems, were grown with I, 2, 4, or 6 mm Fe from ferrous sulfate, ferric citrate, FeEDTA, FeDTPA, FeEDDHA, ferric glucoheptonate, or ferrous ammonium sulfate in the subirrigation solution. FeEDTA and FeDTPA were highly toxic to both species, even at the 1 m Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 11 publications
1
10
1
Order By: Relevance
“…This physiopathy is particularly frequent in geranium due to the pH status of the growth media. The pH level can indeed affect the capability of plants to uptake nutrients, thus leading to nutrient deficiency or toxicity [57][58][59][60][61][62]. An analysis of the nutrient contents in the leaves of the symptomatic plants (Table 3) indicated a high concentration of Fe and Mn, as compared to those that are found in the leaves cultivated using SDS and CS.…”
Section: Foliar Nutrient Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…This physiopathy is particularly frequent in geranium due to the pH status of the growth media. The pH level can indeed affect the capability of plants to uptake nutrients, thus leading to nutrient deficiency or toxicity [57][58][59][60][61][62]. An analysis of the nutrient contents in the leaves of the symptomatic plants (Table 3) indicated a high concentration of Fe and Mn, as compared to those that are found in the leaves cultivated using SDS and CS.…”
Section: Foliar Nutrient Compositionmentioning
confidence: 99%
“…This condition can result in leaf discoloration that, by reducing the photosynthetic efficiency, indirectly affects crop growth [63]. Several studies reported that the toxicity can be due to an overload of Fe in different forms: ferrous sulfate, ferrous ammonium sulfate, ferric glucoheptonate, and ferric citrate are recognized to be moderately toxic to zonal geraniums at high application rates [61], while Fe chelates showed high toxicity when applied in liquid fertilizers [59]. Monteiro and Winterbourn [64] indicated that an excess of iron absorption might induce the production of free radicals that can oxidize the chlorophyll, which thus causes a decrease in the chlorophyll content.…”
Section: Foliar Nutrient Compositionmentioning
confidence: 99%
“…Iron chelates are used to prevent or correct Fe deficiency and have been reported to be more effective than other non-APCA sources of Fe, including Fe citrate, Fe glucoheptonate, and Fe sulfate (Broschat, 2003). Iron chelates, however, have also been found to contribute, possibly in association with substrate pH, to Fe toxicity in certain bedding plants, including marigolds and geraniums (Pelargonium • hortorum) (Albano et al, 1996;Broschat and Moore, 2004;Wik et al, 2006).…”
mentioning
confidence: 99%
“…They reported iron toxicity in cranberry and plant death at treatments of 50 ppm over five weeks, but they noted that plant death could be attributed to interactions with the chelate rather than a direct consequence of iron concentration [10]. Experiments conducted using different iron sources such as ferrous sulfate instead of chelated forms [11] have demonstrated that Fe is not particularly toxic in several plant species previously deemed highly susceptible [12,13]. In the present study, field iron tissue ranged from 143 to 881 ppm among 15 Wisconsin cultivated marshes with no apparent iron adverse reaction (Table 3).…”
Section: Discussionmentioning
confidence: 99%